2021
DOI: 10.3390/clinpract11030070
|View full text |Cite
|
Sign up to set email alerts
|

Peridural Anesthesia and Cancer-Related Survival after Surgery for Pancreatic Cancer—A Retrospective Cohort Study

Abstract: Background: In patients with prostatic and breast cancer the application of peridural anesthesia (PDA) showed a beneficial effect on prognosis. This was explained by reduced requirements for general anesthetics and perioperative opioids as well as a lower perioperative stress level. The impact of PDA in patients with more aggressive types of cancer has not been completely elucidated. Here, we analyzed the prognostic influence of PDA on overall survival after surgery as primary in patients that underwent radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Whereas, Alexander et al. reported no association between EA use and recurrence or overall survival in patients underwent radical resection of pancreatic adenocarcinoma, although subgroup analysis revealed a trend towards a longer overall survival associated with perioperative EA in patients with better differentiation of pancreatic adenocarcinoma ( 48 ). The concentration of LAs may also influence the effects of EA on the oncological outcomes in patients after pancreatic surgery.…”
Section: Effects Of Perioperative Ea On Certain Cancer Typesmentioning
confidence: 99%
“…Whereas, Alexander et al. reported no association between EA use and recurrence or overall survival in patients underwent radical resection of pancreatic adenocarcinoma, although subgroup analysis revealed a trend towards a longer overall survival associated with perioperative EA in patients with better differentiation of pancreatic adenocarcinoma ( 48 ). The concentration of LAs may also influence the effects of EA on the oncological outcomes in patients after pancreatic surgery.…”
Section: Effects Of Perioperative Ea On Certain Cancer Typesmentioning
confidence: 99%
“…11 patients with high concentration of LA (0.375–0.5%) and 96 patients with low concentration (0.15–0.25%) High concentration of ropivacaine improved OS ( p = .04) and was an independent good prognostic factor (HR = 0.65, 95%CI[0.44–0.94]; p = .03) 154 Pancreas Bupivacaine (epidural) Two hundred and fifty-two patients included (n = 88 epidural; n = 164 without epidural) No association with greater recurrence ( p = .87) or all-cause mortality ( p = .85). 175 Pancreas Ropivacaine (peridural) Ninety-eight patients included (70 peridural) No benefits in recurrence or OS 176 Prostate Bupivacaine (epidural) One hundred and forty-eight patients involved (67 epidural) Do not reduce the risk of progression. Do not improve survival.…”
Section: Clinical Investigationmentioning
confidence: 99%
“…The multivariable analysis showed that intraoperative administration of lidocaine improved overall survival (HR = 0.616; 95% CI, 0.290–0.783; P = 0.013) in patients undergoing pancreatectomy [ 12 ]. A clinical study reported that peridural anesthesia with ropivacaine may improve the oncological outcome of PC patients [ 72 ]. Chen et al also reported that intraoperative epidural infusion with a high concentration of ropivacaine was associated with improved overall survival in PC patients undergoing pancreatectomy [ 70 ].…”
Section: The Effects Of Anesthetics On Pc Progression: From Laborator...mentioning
confidence: 99%